Finesse in Maxillofacial Reconstruction: Miniplates Supported Fibula Free Flaps for Enhanced Outcomes- A Report of Two Clinical Cases - Elengkumaran Sankaran; Debothiri Basu; Preetha Parthasarathy; Ronisa Swain; Ravindran Chinnasamy (Journal of Pharmacy and Bioallied Sciences, 2025)
Maxillofacial reconstruction using the archetypical free fibula flap (FFF) can be accomplished utilizing diversified plating techniques. The mini plates and the reconstruction plates or bars exhibit unique characteristics that render them potential advantages, although accompanied by a tolerable measure of disadvantages with respect to successful fixation, favorable clinical outcomes, patient comfort, recovery period, as well as early and late post-operative complications. Although there is substantial evidence on the mechanobiological role of the fixation units in the literature, only sparse data is available that compares the complication profiles of mini plates versus reconstruction bars for a stable fixation during segmental reconstructive procedures. We report here, two cases of highly successful and complication-free maxillary and mandibular reconstructions executed with mini plates as fixation units for the FFF. The intra-operative ease and favorable healing periods observed in both patients exemplify the potential advantages of mini plates as a primary fixation modality in osseous flap reconstructions, underscoring their viability as a preferred alternative to reconstruction bars in select clinical scenarios.